An examination of the extractives of Leonotis species - Kaplan, Errol R (Rhodes University, Faculty of Science, Department of Chemistry, 1966)
Marrubiin and the other two diterpenoids, compounds X and Y, which had previously been isolated from Leonotus leonurus have been reinvestigated. Although the structure for marrubiin is well known its stereochemistry has been the subject of protracted discussion and is by no means secure except at Câ‚… and Câ‚ â‚€ . N.M.R. spectral evidence showed that the lactone ring was cis-fused and Î²-orientated. Dehydration experiments carried out by previous workers were repeated, in order to resolve the residual uncertainty regarding the stereochemistry at Câ‚‰, an attempt was made to prepare iodoacetyl marrubic acid for X-ray crystallographic studies. Compound Y, Câ‚‚â‚€Hâ‚‚â‚ˆ0â‚ƒ, a triply-unsaturated compound was shown by spectral studies to contain a furan ring and an Î±,Î²- unsaturated keto-group. It possesses a hydroxyl group incapable of acetylation, but readily removed by alkali and dehydrating agents to yield a tetraunsaturated compound, anhydro~Y; the hydroxyl is thus tertiary, Isolation of 1:2:5-trimethylnaphthalene on dehydrogenation indicated a relationship with the labdane diterpene group and supported the Câ‚‚â‚€ formula, The position of the Î±,Î²-unsaturated keto-group was resolved by interpretation of the ultraviolet spectra of degradation products and also by isolation of 1:2:3:5- trimethylnaphthalene on dehydrogenation of a suitable grignard product, The presence of a Î²-substituted furan was further indicated by colour reactions and confirmed by mass and n.m.r. spectra. The skeleton of compound Y is correlated with marrubiin via "iso-ambreinolide " and its stereochemistry is discussed. Further stereochemical assignments are postulated from the study of the n.m.r. spectra. Compound X, Câ‚‚â‚€Hâ‚‚â‚ˆ0â‚…, was shown by spectral and chemical evidence to be a diterpenoid dilactone containing an ether bridge between Câ‚‰ and Câ‚ â‚ƒ Isolation of 1:2:5 trimethylnaphthal ene on dehydrogenation showed it to be closely related to marrubiin, This was supported by n.m.r. spectral results. A structure for compound X is proposed and the stereochemistry discussed. The aerial portions of Leonotis leonitis were also extracted and shown to contain a new compound, compound R. Preliminary investigation showed that it was a dilactone containing a furan ring, The n.m.r. spectrum of the compound is discussed.
Keywords: Leonotis -- Analysis; Botanical chemistry; Chemistry, Analytic; Chemistry, Organic